Ferroptosis-Related Lipid Peroxidation Biomarkers as Early Predictors of Diabetic Kidney Dysfunction - Naif , Mohammed Abdul Ghani; Mohammed, Yaseen Jasem (American Journal of Bioscience and Clinical Integrity, 2026)
Diabetic kidney disease (DKD) is a major cause of end-stage renal disease (ESRD) worldwide. This condition is significantly more prevalent among Iraqis. The potential of ferroptosis as a biomarker for early prediction of kidney dysfunction has not yet been explored in a Middle Eastern cohort. Ferroptosis is an iron-dependent form of regulated cell death driven by lipidd peroxidation. Further, an increasing number of literature report ferroptosis to be a pathogenic mechanism in DKD. To achieve this, 120 patients with T2DM who had never had kidney disease were included in the study. Blood specimens were obtained from them to determine kidney function and the concentrations of ferroptosis-related biomarkers. Moreover, we correlated these biomarkers with the severity of kidney disease in T2DM patients. Among total 165 participants, we included 40 healthy controls (HC), 45 T2DM without DKD, 42 early DKD, and 38 advanced DKD. Quantification of serum and urinary biomarkers was done using ELISA and colorimetric assessment methods. The kidney functions were assessed using estimated GFR, UACR, serum creatinine and blood urea nitrogen. ROC analysis assessed the accuracy of the prediction. Increase in MDA, 4-HNE, ACSL4 and TFR1 across various stages of the disease; Decrease in GPX4 and GSH (all p<0.001) This combined biomarker panel (MDA, 4-HNE, GPX4, and ACSL4) achieved an AUC of 0.928 (95% CI: 0.886–0.970), which was better than any of the individual biologic markers just taken alone. MDA is the most negatively correlated with eGFR and positively correlated with UACR. To sum up, it is evident that ferroptosis-associated lipid peroxidation biomarkers, particularly a combined panel, are highly predictive of early diabetic kidney dysfunction in the Iraqi population, and hence can be clinically actionable early detection tools.